Haploinsufficiency of osterix in chondrocytes impairs skeletal growth in mice - Cheng, Shaohong (American Physiological Society, 2013)
Osterix (Osx) is essential for both intramembranous or endochondral bone formation. Osteoblast-specific ablation of Osx using Col1α1-Cre resulted in osteopenia, because of impaired osteoblast differentiation in adult mice. Since Osx is also known to be expressed in chondrocytes, we evaluated the role of Osx expressed in chondrocytes by examining the skeletal phenotype of mice with conditional disruption of Osx in Col2α1-expressing chondrocytes. Surprisingly, Cre-positive mice that were homozygous for Osx floxed alleles died after birth. Alcian blue and alizarin red staining revealed that the lengths of skeleton, femur, and vertebrae were reduced by 21, 26, and 14% (P < 0.01), respectively, in the knockout (KO) compared with wild-type mice. To determine if haploid insufficiency of Osx in chondrocytes influenced postnatal skeletal growth, we compared skeletal phenotype of floxed heterozygous mice that were Cre-positive or Cre-negative. Body length was reduced by 8% (P < 0.001), and areal BMD of total body, femur, and tibia was reduced by 5, 7, and 8% (P < 0.05), respectively, in mice with conditional disruption of one allele of Osx in chondrocytes. Micro-CT showed reduced cortical volumetric bone mineral density and trabecular bone volume to total volume in the femurs of Osx(flox/+);col2α1-Cre mice. Histological analysis revealed that the impairment of longitudinal growth was associated with disrupted growth plates in the Osx(flox/+);col2α1-Cre mice. Primary chondrocytes isolated from KO embryos showed reduced expression of chondral ossification markers but elevated expression of chondrogenesis markers. Our findings indicate that Osx expressed in chondrocytes regulates bone growth in part by regulating chondrocyte hypertrophy.